Learning Loss during Covid-19 Pandemic in Indonesia and the Strategies to Minimize It - Agus Wahyudi (Journal of English Education and Linguistics, 2021)
The current coronavirus (Covid-19) pandemic is having a profound impact, not only on people’s health, but also on how they learn, work and live. Amongst the most important challenges created by Covid-19 is how to adopt a system of education built around physical schools. Based on the Higher Education Law number 12 of 2012, Article 31 concerning Distance Education is a learning process that is carried out remotely through the use of various communication and information media. With the implementation of distance learning during the pandemic and the problems that occurred above, it turns out that this decision has the risk of causing learning loss for students. Asian Development Bank (ADB) estimates that school closures due to the Covid-19 coronavirus pandemic have made many students in Indonesia lose learning opportunities Based on the Human Capital Index 2020, Indonesia has a LAYS of 7.83 years. This research was conducted using qualitative descriptive research. This study aims to reveal the facts, phenomena, and circumstances that existed during the research process by providing what actually happened when learning activities took place with distance education. This burden is the responsibility of all elements of education, especially the state in facilitating the continuity of schools for all educational stakeholders to conduct distance learning. How should Indonesia plan, prepare, and overcome the Covid-19 recovery, in order to reduce the losses to the world of education in the future